UnWholly - Shusterman, Neal. (New York : Simon & Schuster BFYR, 2012)
Thanks to Connor, Lev, and Risa, and their high-profile revolt at Happy Jack Harvest Camp, people can no longer turn a blind eye to unwinding. Ridding society of troublesome teens and, in the same stroke, providing much- needed tissues for transplant might be convenient, but its morality has finally been brought into question. Cam is a teen who does not exist. He is made entirely out of the parts of other unwinds. Cam, a 21st century Frankenstein, struggles with a search for identity and meaning, as well as the concept of his own soul, if indeed a rewound being can have one.
Sequel to: Unwind.
860
Keywords: Fugitives from justice -- Juvenile fiction; Survival -- Juvenile fiction; Revolutionaries -- Juvenile fiction; Identity (Philosophical concept) -- Juvenile fiction; Science fiction